A V4 országok regionális koherenciája az EU integráció kivándorlásra gyakorolt hatásának tükrében - Koudela, Pál (Közép-Európai Közlemények, 2016)
Severe changes occurred in east-west migration from the V4 countries, its regional role both geopolitically and in regards of its homogeneity, during the period since their EU accession. The four countries have similarities and differences both in immigration from the Baltic countries and in emigration to western countries. The latter is rarely examined field, especially in a comparative way, even less examined as embedded into a regional concept; for this reason we deal with it in more detail. Both economic and demographic differences are determinant alone in each country, but recent conflicts – which called EU integration in question (especially along with BREXIT) – are also important for preserving the regional integrity of the Visegrad countries. Each of the four countries has different targets in outward migration, different migration methods and role in the receiving countries. Poland is the largest sending population, it has the largest Diasporas, but Hungarian émigré chose more often longer term stay out. The Czech emigrants are far less than the other considering both target countries, their number and their rate compared to the population of the sending country.